The cyanotoxins occurrence in water and fresh foods: human health implications - España Francis, Nelfa Elizabeth; Gomez Luna, Liliana María (Ingeniería Química y Desarrollo, 2024)
The cyanotoxins occurrence in water, and their incorporation into the food chain have caused numerous reports of health damage. This study presents a systematic-critical review on the presence and implications of cyanotoxins in water and fresh foods, considering their potential impact on human health. The applied methodology corresponds to a critical-narrative analysis of research published in institutional repositories and high-impact databases (PubMed, Crossref, Google Scholar, Scopus) considering the last 10 years of documentary validity. The results demonstrate a recognition of the impact of human activities and climate change on the increasing incidence of cyanotoxins on human well-being, with negative implications, related to gastrointestinal symptoms, liver conditions and damage to the nervous system, the impact being relevant. of microcystins and cylindrospermopsins. Emphasis is placed on the need to obtain precise data on the toxicological charge in both water, biomass, and fresh foods, to establish the pertinent restrictions in order to provide health guarantees. Governments must take measures to prevent the risk associated with the presence of cyanotoxins, with training and capacity building for research and management being necessary in vulnerable contexts. Mitigation of the impacts of cyanotoxins must be treated from a communication and instructional point of view. It is important to develop awareness campaigns to improve perception of this emerging risk, which often compromises the lives of human beings.
Keywords: cyanotoxins; foods; health damages; toxicity; water